2011
DOI: 10.1590/s1983-41952011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Concreto submetido a vibrações nas primeiras idades

Abstract: This study describes the early-age behavior of high-strength concrete made with high initial strength cement and exposed to an environment with vibrations. A sequence of tests is presented which includes the molding of concrete specimens subjected to traffic vibrations, as well as a mechanical characterization and steel-concrete bonding tests. Results indicated that early age concrete specimens subjected to vibrations undergo losses in tensile strength and in their modulus of elasticity. Such reduction in stif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…Additionally, Figure 5 also shows that the cracking strength was the most sensitive to the variables in this section, and then it followed the ultimate tensile strength and strain. These results were similar to the studies on compressive strength [34], bond strength [35], splitting strength [36] of early-age concrete that was subjected to vibrations during this period.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Additionally, Figure 5 also shows that the cracking strength was the most sensitive to the variables in this section, and then it followed the ultimate tensile strength and strain. These results were similar to the studies on compressive strength [34], bond strength [35], splitting strength [36] of early-age concrete that was subjected to vibrations during this period.…”
Section: Resultssupporting
confidence: 89%
“…Their results showed that if the vibration occurred before the final set, there would be a considerable reduction in the compressive and bond strengths of early-age bridge deck repairs [34]. In particular, studies have shown that, when subjected to vehicle-induced vibrations during the period between the initial set and the final set, concrete bridge deck repairs experienced tensile strength and elastic coefficient losses [35]. Fernandes pointed out that special care must be taken with regard to the tensile strength of concrete repairs, because its reduction can have a negative effect on the usability of a bridge deck, and it can result in a greater deflection [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though forced vibration techniques can increase the accuracy of the modal identification of the composite beam, it has to be taken into account that the application of an external vibration during the curing period of the cementitious materials may potentially affect the development of the mechanical properties, particularly during the setting time when bonds are being formed in the cement matrix that can be damaged due to the vibrations. This issue was studied by several authors, and it was found that excessive vibration during the curing process can affect the elastic modulus by almost 10%. Also in the work of Hong and Park, it was found that even small vibrations (with maximum accelerations of 14.4 mg at 5 Hz) can have a relevant impact in the concrete curing process and affect its mechanical properties.…”
Section: Improvements To the Ambient Vibration Methodsmentioning
confidence: 99%
“…The impact of mechanical vibration on the performance of cement-based materials has been extensively studied, as it is the most commonly encountered type of vibration during construction and directly affects the quality and service life of concrete structures [ 5 , 6 ]. Vibration is a macroscopic physical process, and the microstructure of cement-based materials is altered during this process [ 7 ].…”
Section: Introductionmentioning
confidence: 99%